Sex-Specific Associations of Anxiety With Left Ventricular Hypertrophy and Transmural Dispersion of Repolarization in Hypertensive Patients - Zhu, Ling; Cui, Qianwei; Zhang, Yong; Liu, Fuqiang; Zhao, Jingsha; Wang, Junkui (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies have shown that individuals with hypertension and anxiety have a higher mean left ventricular mass index (LVMI) and QTc dispersion. We explored the associations between anxiety and left ventricular hypertrophy (LVH) and between anxiety and transmural dispersion of repolarization (TDR) (as detected by T peak-T end interval/QT interval, Tp-Te/QT ratio) in patients with hypertension. Methods: A total of 353 patients with uncomplicated hypertension from Shaanxi Provincial People's Hospital were enrolled between 2017 and 2021. Anxiety was defined as a HAM-A score ≥14. Logistic regression models were used to estimate the association between HAM-A and LVH. The association between HAM-A score and Tp-Te/QT was estimated using linear regression. Results: Participants were divided into two groups based on the presence of anxiety. Left ventricular mass index was significantly higher in patients with hypertension and anxiety than in those with hypertension without anxiety (no anxiety: 84.36±23.82, anxiety: 105.75±25.45, g/m2, P<0.001). HAM-A score was positively correlated with LVMI (r=0.578, P<0.001) and with Tp-Te/QT (r=0.252, P<0.001). Logistic regression models showed that patients with hypertension and anxiety were at higher risk of LVH than were patients with hypertension without anxiety (adjusted OR, 2.44, 95% CI, 1.35–4.43, P=0.003). Linear regression analysis showed that HAM-A score was associated with Tp-Te/QT ratio (adjusted β, 0.001, 95% CI, 0.001–0.002, P=0.013). There was an interaction between sex and anxiety for LVH risk (P for interaction = 0.035) and for increased Tp-Te/QT (P for interaction = 0.014). After stratification by sex, anxiety was associated with increased risk for LVH in males with hypertension (adjusted OR, 5.56, 95% CI, 2.07–14.98, P=0.001), but not in females (adjusted: OR, 1.44, 95% CI, 0.64–3.26, P=0.377) with hypertension. HAM-A score was also positively associated with Tp-Te/QT ratio in male (adjusted β, 0.002, 95% CI, 0.001–0.003, P<0.001), but not in females (adjusted β, 0.001, 95% CI, -0.0002–0.002, P=0.165). Conclusion: Our results indicated that anxiety was associated with LVH and with increased TDR in males with hypertension, but not in females with hypertension.